The Efficacy of Specific Activation of D1-class Dopamine Receptors to Enhance Motor Recovery in Mice Following Cortical Photothrombotic Stroke - Gower, Annette (Université d'Ottawa / University of Ottawa, 2018)
Stroke is a widespread condition, which often leaves survivors with lasting deficits in motor function, however, physical rehabilitation is the only treatment available after the acute period. A large body of preclinical literature suggests dopamine-augmenting drugs, could enhance motor recovery following stroke. Unfortunately, mixed clinical results have prevented the implementation of such treatments, possibly due to the wide variety of G protein-coupled receptors these drugs can activate. Using a mouse photothrombosis stroke model and a battery of motor and sensorimotor behavioural tests, the current study aims to demonstrate proof of principle for the use of D1-class dopamine receptor agonists to enhance poststroke motor recovery and to evaluate the role of aerobic exercise rehabilitation in an asynchronous study design. The effect of light-dark cycle on behavioural outcome (horizontal ladder test, adhesive removal test, cylinder test) and histological outcome (infarct size) in photothrombotic stroke was evaluated in order to optimize the stroke model, but no there was no evidence of differences between strokes occurring during the light or dark period of a mouse’s circadian rhythm. A bioactive, suboptimal dose of D1-agonist dihydrexidine, was determined by evaluating its effect on locomotor activity and its ability to increase expression of immediate early gene c-fos. Using the determined dose, studies evaluating the efficacy of 7-days and 2-days of dihydrexidine administration on poststroke motor recovery, were performed, indicating efficacy of a 7-days, but not of a 2-days, course of treatment. The 7-days dihydrexidine treatment resulted in accelerated recovery as compared to a control group receiving saline. This work demonstrates, for the first time, proof of principle for the use of specific activation of D1-class dopamine receptors to enhance motor recovery following stroke.
Keywords: stroke recovery; D1-class dopamine receptors; motor recovery; pharmacotherapy